Effect of root extract on nodulation of cowpea - Araújo, Fábio F.; Medeiros, Joselito S. (Pesquisa Agropecuaria Brasileira, 1992)
This work studied the effects of root extract on nodulation of cowpea (Vigna unguiculata (L.) Walp.) in the greenhouse. Two strains of Bradyrhizobium (MAC-2 and RBGm-28) were pre-tested with the extracts of cowpea roots, and their symbiotic performances were analysed. In the association cowpea/RBGm-28, the root extract influenced significantly some of the stages of the symbiotic process. In that case a decrease in the number of nodules formed and in nodule dry weights was observed. The time of inoculum culturing influenced significantly the dry weight and the plant leaf area.